2012
DOI: 10.15208/beh.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of real exchange rate volatility on economic growth: Kenyan evidence

Abstract: This paper examines the impact of real exchange rate volatility on economic growth in Kenyan. The study employed the Generalized Autoregressive Condition of Heteroscedasticity (GARCH) and computation of the unconditional standard deviation of the changes to measure volatility and Generalized Method Moments (GMM) to assess the impact of the real exchange rate volatility on economic growth for the period January 1993 to December 2009. Data for the study was collected from Kenya National Bureau of Statistics, Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
(9 reference statements)
4
13
1
Order By: Relevance
“…The implication is that for Nigeria to ensure sustainability in gross domestic product growth, the exchange rate must be favourable while interest rate reduced to barest minimum to allow access to credit at low cost. This is in agreement with [8], [13], [20], [21], [22] and [27] for Nigeria, [15] for Kenya, [17] for 18 developing countries of the world, [23] for Pakistan and [28] on contractional effect of high interest rate on annual GDP of major industrial countries. Finally, through the Granger Causality analysis, it was empirically established that exchange rate and interest rate are not determinants of real gross domestic product growth in Nigeria.…”
Section: Discussion Of Findings In Relation To Previous Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…The implication is that for Nigeria to ensure sustainability in gross domestic product growth, the exchange rate must be favourable while interest rate reduced to barest minimum to allow access to credit at low cost. This is in agreement with [8], [13], [20], [21], [22] and [27] for Nigeria, [15] for Kenya, [17] for 18 developing countries of the world, [23] for Pakistan and [28] on contractional effect of high interest rate on annual GDP of major industrial countries. Finally, through the Granger Causality analysis, it was empirically established that exchange rate and interest rate are not determinants of real gross domestic product growth in Nigeria.…”
Section: Discussion Of Findings In Relation To Previous Studiessupporting
confidence: 89%
“…In the experience of other countries in Africa, [14] established that economic growth in Côte d'Ivoire has been negatively affected by exchange rate volatility. In the same manner, [15] observed that Kenya's international competitiveness deteriorated owing to high volatility in exchange rate. Away from the continent of Africa, [16] proved that low fluctuation in exchange rate has enhanced economic growth in Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 82%
“…This implies that the volatility of the Rand/Pula exchange rate has no impact on Botswana's economic growth. The negative but insignificant impact of exchange rate volatility on Botswana's economic growth mirrors the findings of Kaur et al (2019) and Musyoki et al (2012) Labour Force (LF) is significantly related to economic growth rate. This shows that Labour Force is positively related to economic growth.…”
Section: Gmm Estimation Resultssupporting
confidence: 72%
“…Dickson (2012) also explains that economic growth is responsive to exchange rate volatility in both the short and long run, in the Nigerian context. In another study by Musyoki et al (2012), their result shows that real exchange rate in Kenya was very volatile and exhibit appreciating trend in the foreign currency, implying that international competitiveness is hampered and reflected a negative impact on economic growth of Kenya.…”
Section: Historical Backgroundmentioning
confidence: 97%
“…Under this arrangement, the authorized dealers were permitted to deal in foreign exchange on their own accounts for onward sale to their customers. These exchange rate regimes have had some implication for economic performance (NDIC, 2016).…”
Section: Historical Backgroundmentioning
confidence: 99%